2019
DOI: 10.2147/prbm.s211873
|View full text |Cite
|
Sign up to set email alerts
|

<p>A latent profile approach for the study of internet gaming disorder, social media addiction, and psychopathology in a normative sample of adolescents</p>

Abstract: Background For a small minority of individuals, the overuse of digital technologies has been associated with negative factors, including psychological distress and psychopathological symptoms. Two technology-based addictions – internet gaming disorder (IGD) and social media addiction (SMA) – have been found to be related to comorbid disorders and impulsivity especially in adolescents and emerging adults’ populations, but results in this field are inconclusive Purpose Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 36 publications
4
37
1
Order By: Relevance
“…Finally, examining the mediating associations between Dark Triad traits and social media addiction requires the inclusion of gender as an important variable to get the full picture, since significant gender effects were generally found among the aforementioned associations. Some studies have reported that girls usually share and post more selfies on social networks than boys [ 30 , 34 , 48 , 49 , 50 ], and other studies have reported an association between narcissism and selfie-posting and editing behavior among men [ 27 , 31 , 48 ]. Similarly, Arpaci et al’s study [ 48 ] demonstrated the influence of selfie behavior on narcissism but only in men.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, examining the mediating associations between Dark Triad traits and social media addiction requires the inclusion of gender as an important variable to get the full picture, since significant gender effects were generally found among the aforementioned associations. Some studies have reported that girls usually share and post more selfies on social networks than boys [ 30 , 34 , 48 , 49 , 50 ], and other studies have reported an association between narcissism and selfie-posting and editing behavior among men [ 27 , 31 , 48 ]. Similarly, Arpaci et al’s study [ 48 ] demonstrated the influence of selfie behavior on narcissism but only in men.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics can also make people more vulnerable to behavioral addiction [7] in the form of habitual checking or excessive use of smartphones. Previous studies have reported that excessive smartphone use in adolescents is associated with psychopathologies (i.e., depression, anxiety, high-stress levels, and low mood) and behavioral problems [8,9], because adolescents are easily affected by external stimulus, interpersonal issues, and emotional changes. Another study on young adults suggested that excessive smartphone use is related to high stress, and it is also inversely related to academic performance, as well as life satisfaction [10].…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few recent studies have simultaneously explored the use of multiple technological instruments during adolescence highlighting various technology‐related behavior patterns (Carras, Van Rooij, Van de Mheen, Musci, Xue & Mendelson, 2017; Cerniglia, Griffiths, Cimino et al ., 2019; Lee et al ., 2018). In particular, Carras and colleagues (2017) investigated problematic videogame use and online social interactions identifying two groups of heavy gamers who differed in their level of online communication.…”
Section: Introductionmentioning
confidence: 99%
“…However, both groups showed more depressive symptoms than normative gamers . In a similar study, social media addiction and problematic videogame use were investigated (Cerniglia, Griffiths, Cimino et al ., 2019). The results revealed two profiles of users in the 14–15 year age group and three profiles in the 16–17 year age group.…”
Section: Introductionmentioning
confidence: 99%